2009
DOI: 10.1111/j.1439-0426.2009.01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Life-history traits of invasive bighead gobyNeogobius kessleri(Günther, 1861) from the middle Danube River, with a reflection on which goby species may win the competition

Abstract: SummaryLife history traits of an invasive population of bighead goby Neogobius kesslerei (Gu¨nther, 1861) from the middle Danube, including absolute and relative fecundity, egg size, number of spawning batches and size at first maturation, were examined and evaluated within an epigenetic context. Ripe bighead goby females attained 42.8-142.5 mm L S , with absolute fecundities ranging from 669 to 5646 eggs (mean 2109 eggs), and relative fecundities of 61.6-174.0 eggs g )1 body weight (mean 119.6 eggs). Egg diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 15 publications
0
41
0
Order By: Relevance
“…And, the theory of alternative ontogenies and invasive potential develops this idea further as it postulates that the wider is the range between the most generalized and the most specialized phenotype a species can generate, the wider is its invasive potential (Kováč, 2010;. Indeed, the existence of alternative ontogenies has been observed in our previous studies devoted to invasive populations of N. melanostomus and bighead goby Neogobius kessleri (Günther 1861) (Balážová-L'avrinčíková and Kováč et al, 2009), as well as topmouth gudgeon Pseudorasbora parva (Temminck and Schlegel, 1842), where the predictions derived from the above hypothesis were tested statistically for the first time . In the latter study, two of three quantitative parameters of life-history traits examined in three invasive populations of topmouth gudgeon supported the hypothesis, whereas the third one remained questionable but not sufficient to reject it.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…And, the theory of alternative ontogenies and invasive potential develops this idea further as it postulates that the wider is the range between the most generalized and the most specialized phenotype a species can generate, the wider is its invasive potential (Kováč, 2010;. Indeed, the existence of alternative ontogenies has been observed in our previous studies devoted to invasive populations of N. melanostomus and bighead goby Neogobius kessleri (Günther 1861) (Balážová-L'avrinčíková and Kováč et al, 2009), as well as topmouth gudgeon Pseudorasbora parva (Temminck and Schlegel, 1842), where the predictions derived from the above hypothesis were tested statistically for the first time . In the latter study, two of three quantitative parameters of life-history traits examined in three invasive populations of topmouth gudgeon supported the hypothesis, whereas the third one remained questionable but not sufficient to reject it.…”
Section: Introductionmentioning
confidence: 96%
“…Such an expansive dispersion of N. melanostomus is associated with the species' tolerance of various range of environmental conditions (Moskal'kova, 1996;Charlebois et al, 1997;Young et al, 2010), a wide range of diet and flexibility in feeding behaviour (Shemonaev and Kirilenko, 2009;Števove and Kováč, 2013), aggressive behaviour during reproduction period, high reproduction rate and parental care, larger body size compared with other benthic species (Charlebois et al, 1997;Jude, 1997), as well as flexibility in life-history traits (Gutowsky and Fox, 2012). Indeed, previous studies focused on invasive N. melanostomus have revealed that this species has the capability to generate forms with life-history traits that are different between its native populations and its non-native populations (MacInnis and Corkum, 2000;L'avrinčíková and Kováč, 2007;Kováč et al, 2009). Changes in life-history traits, however, have not only been observed in N. melanostomus but in several other invasive fish species, too (Feiner et al, 2012;.…”
Section: Introductionmentioning
confidence: 99%
“…In short, epigenesis, the mechanism of ontogenies, creates in every generation alternative variations that enable the organism to survive in changing environments as either altricial (generalized) or precocial (specialised) forms. As a result, the life history of each population and/or species can vary from generation to generation along a continuum between the most generalized and the most specialized extremes [9,10]. This pattern has been documented in some other invasive species such as bighead goby and/or round goby [10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the life history of each population and/or species can vary from generation to generation along a continuum between the most generalized and the most specialized extremes [9,10]. This pattern has been documented in some other invasive species such as bighead goby and/or round goby [10].…”
Section: Introductionmentioning
confidence: 99%
“…and/or 3) do the two species occupy the same dietary niche -do they compete for food? Along with our previous studies devoted mainly to the first of these questions (L'avrinčíková et al, 2005;L'avrinčíková and Kováč, 2007;Kováč et al, 2009;Grul'a et al, 2012), this study contributes in searching for answers of all the three. Within this context, it is essential to understand the use of food resources by the invading fish, including their primary prey and feeding ecology.…”
Section: Introductionmentioning
confidence: 99%